2010
DOI: 10.1111/j.1472-9733.2010.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of nasal obstruction in patients with allergic rhinitis

Abstract: Summary Nasal obstruction is a crucial symptom in allergic rhinitis (AR) patients and may affect the quality of life. It is caused mostly by nasal mucosal obstruction, and to a lesser extent, fluid secretion. Mucosal congestion is primarily a vascular phenomenon comprising vasodilatation of capacitance vessels (cavernous sinus) and oedema formation due to plasma leakage from post‐capillary venules. The nose has a complex microvascular anatomy consisting of capacitance vessels, arteriovenous anastomosis, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Capillaries are present in the surface layer while venous sinusoids are abundant in the anterior part of the inferior septum (Figure 5A,C). 3 As shown in Figure 5B, α-SMA-negative/CD31-positive capillaries were broadly present on the surface are of septum mucosa (Figure 5B, left picture). α-SMA-positive/CD31-negative elastic fibers were observed at high-magnification (Figure 5B, right picture).…”
Section: The Effect Of 8-iso-pge 2 On Nasal Capillary and Venous Sinusoidsmentioning
confidence: 82%
See 1 more Smart Citation
“…Capillaries are present in the surface layer while venous sinusoids are abundant in the anterior part of the inferior septum (Figure 5A,C). 3 As shown in Figure 5B, α-SMA-negative/CD31-positive capillaries were broadly present on the surface are of septum mucosa (Figure 5B, left picture). α-SMA-positive/CD31-negative elastic fibers were observed at high-magnification (Figure 5B, right picture).…”
Section: The Effect Of 8-iso-pge 2 On Nasal Capillary and Venous Sinusoidsmentioning
confidence: 82%
“…*p < .05; **p < .01 3.4 | The effect of 8-iso-PGE 2 on TP-mediated endothelial barrier disruption Vasodilation of sinusoid vein and plasma leakage due to vascular hyperpermeability in post-capillary vessels are mainly involved in the induction of nasal obstruction. 3 We previously demonstrated that endothelial TP activation results in vascular hyperpermeability both in vitro and in vivo. 14 To examine whether the 4 candidates mediate TP-induced vascular hyperpermeability, we measured trans endothelial resistance (TER), indexed as vascular permeability, by using BAECs.…”
Section: F I G U R Ementioning
confidence: 97%
“…Nasal congestion is a difficult symptom to treat and manage in AR. Mucosal engorgement, edematous swelling due to increased blood flow, and vascular hyperpermeability cause nasal congestion 11 . The nasal mucosa is covered by large, sinusoidal veins, most of which possess thin walls and store a large amount of blood.…”
Section: Introductionmentioning
confidence: 99%
“…9 Nasal tk;1obstruction is noted to be the most commonly presenting and debilitating symptom of allergic rhinitis, and it is caused by vasodilation of arterioles, venules, and capillaries as well as an increase in vessel permeability that leads to edema. 10 …”
mentioning
confidence: 99%
“…9 Nasal tk;1obstruction is noted to be the most commonly presenting and debilitating symptom of allergic rhinitis, and it is caused by vasodilation of arterioles, venules, and capillaries as well as an increase in vessel permeability that leads to edema. 10 Allergic rhinitis was traditionally classified as either seasonal or perennial based on the time of occurrence of symptoms. This classification has ceased to be used since the development of new Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines for the diagnosis and classification of allergic rhinitis.…”
mentioning
confidence: 99%